The Impact of Corporate Governance and Firm Characteristics on the Timeliness of Corporate Internet Reporting in Indonesia - Devi Anna, Yane; Rahayu, Sri (International Journal of Engineering and Technology, 2018)
This paper presents a discussion about how timely the company's internet reports are published by Indonesian companies listed on the Indonesia Stock Exchange. Taking into account the importance of corporate governance and company characteristics, this study examined the company's 2016 annual reports and the timeliness of their internet reporting based on website snapshots. The results proved that the timeliness of corporate internet reporting has an important relationships with audit committee and profitability. However, it was also revealed that there was no significant effect of board independence, board financial expertise, board size, company size and leverage on the timeliness of the company's internet reporting.Â